Simultaneous Chromophobe renal cell carcinoma and squamous renal cell carcinoma - Robles Luis; Rodrigo Isabel; Pereda Teresa; Fúnez Rafael; González Carlos (BMC, 2007)
Abstract Chromophobe renal cell carcinoma (CHRC) is a neoplasm of the kidney with clinicopathologic peculiarities that seems to be of better prognosis than conventional renal cell carcinoma. Classical and eosinophilic types are the two histological variants recorded. Also, it has been described in association with carcinoma of collecting ducts, conventional renal cell carcinoma and sarcomatoid renal cell carcinoma. Squamous renal carcinoma is a very rare neoplasm with a malignant course. We describe a case of simultaneous chromophobe renal cell carcinoma with squamous cell carcinoma, finding which, to the best of our knowledge, has not previously been reported.